Analisis Daya Dukung Lateral Bored Pile Ø 80 Cm dengan Menggunakan Uji Beban Lateral dan Menggunakan Metode Elemen Hingga pada Proyek Menara BRI - Medan - Rizky Simanjuntak; Roesyanto Roesyanto; Syiril Erwin Harahapan (Syntax Corporation Indonesia, 2024)
Bored pile foundations are deep foundations that are often used in the construction of large construction sites located in dense areas with the consideration of reducing noise and the influence of vibrations that would occur if pile foundations were used. This analysis aims to calculate the lateral bearing capacity of the bored pile foundation based on the results of analytical calculations using the Broms method, the Davisson method, the Chin method, the Mazurkiewich method, and analyzing the displacement of the bored pile foundation based on loading tests in the field. and the results of soil modeling with Allpile and finite element methods with the Mohr-Coulomb soil model, and the Hardening Soil model. Based on the analysis that has been carried out, the ultimate bearing capacity of the bored pile based on SPT data using the Broms method is 18.92 tons, while the results of the interpretation of the loading test using the Davisson method are 18 tons, the Chin method is 18.98 tons, and the Mazurkiewich method is 19 tons. For the large deflection of a single bored pile with a load of 200% with the Allpile program the large deflection that occurs is 4.25 mm and analysis based on FEM PLAXIS 3D using soil modeling with Mohr - Coulomb large deflection of 3.0 mm and soil modeling with Hardening Soil 2.99 mm.